A New Study in the Field of Ukrainian Dialectology - Jankowiak, Mirosław (Slavistica Vilnensis, 2025)
HLIBČUK NATALIJA, KOSTIV OKSANA, 2023, Ukrajins’ka dialektolohija, L’viv: LА «Piramida», s. 552 [ГЛІБЧУК НАТАЛІЯ, КОСТІВ ОКСАНА, 2023, Украïнська діалектологія, Львів: ЛА «Піраміда», с. 552], ISBN 978-966-441-768-3. The presented book entitled Ukrajins’ka dialektolohija [Ukrainian dialectology, 2023] by Natalia Hlibčuk and Oksana Kostiv is the first textbook for students of Ukrainian philology published after 1991. Although Ukrainian dialectology has a rich and long history and can boast many important works in this field, in its history it has had only a few textbooks on Ukrainian dialectology. The reviewed publication is therefore a very important book for Ukrainian linguistics. The authors have used a classic structure, typical for this type of publication, supplementing it with the results of the latest field research on Ukrainian dialects.